On Complementability of Nonmetacyclic Subgroups in Finite A-Groups - Baryshovets, P. P. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We study groups G that satisfy the following conditions: (i) G is a finite solvable group with nonprimary metacyclic second subgroup and (ii) all Sylow subgroups of the group G are elementary Abelian subgroups. We describe the structure of groups of this type with complementable nonmetacyclic subgroups.